Prevalence of pathological internet use among adolescents in Europe: demographic and social factors - Durkee, Tony; Kaess, Michael; Parzer, Peter; Brunner, Romuald; Resch, Franz (Addiction, 2012)
Aims To investigate the prevalence of pathological internet use (PIU) and maladaptive internet use (MIU) among adolescents in 11 European countries in relation to demographic, social factors and internet accessibility. Design Cross-sectional survey. Setting The 7th Framework European Union (EU) funded project, Saving and Empowering Young Lives in Europe (SEYLE), is a randomized controlled trial (RCT) evaluating interventions for risk behaviours among adolescents in Austria, Estonia, France, Germany, Hungary, Ireland, Israel, Italy, Romania, Slovenia and Spain, with Sweden serving as the coordinating centre. Participants A total of 11 956 adolescents (female/male: 6731/5225; mean age: 14.9 ± 0.89) recruited from randomly selected schools within the 11 study sites. Measurements Internet users were classified by gender into three categories: adaptive, maladaptive and pathological, based on their score in the Young Diagnostic Questionnaire for Internet Addiction (YDQ). Findings The overall prevalence of PIU was 4.4%; it was higher among males than females (5.2% versus 3.8%) and differed between countries (χ2 = 309.98; d.f. = 20; P < 0.001). PIU correlated significantly with mean hours online and male gender. The highest-ranked online activities were watching videos, frequenting chatrooms and social networking; significantly higher rates of playing single-user games were found in males and social networking in females. Living in metropolitan areas was associated with PIU. Students not living with a biological parent, low parental involvement and parental unemployment showed the highest relative risks of both MIU and PIU. Conclusions Across a range of countries in Europe, using the Young Diagnostic Questionnaire for Internet Addiction yields a prevalence of ‘pathological internet use’ of 4.4% among adolescents, but varies by country and gender; adolescents lacking emotional and psychological support are at highest risk.